Foundry production scheduling by Adexa in an oilfield service company - Wang, Xiaojun (2014)
Production scheduling in company SLB requires significant manual planning power due to the large volume of work orders. SLB is looking for alternatives to replace manual planning with computer planning to save planning costs and realize its investment on Adexa. Adexa is a tool which can generate optimized production schedules for manufacturing companies. This thesis project studies the foundry production scheduling using Adexa in SLB. The available capacity for work centers and production process flows in foundry and stage machining are studied. Adexa model for foundry is built by defining the inputs of the work centers. The inputs are further fine-tuned based on the loading percentage calculations. A test case for foundry is designed to investigate the planning logic of Adexa in balancing the demand with supply. The result shows that Adexa’s planning logic matches the SLB’s manual planning logic. Lastly, results of trial runs of Adexa without capacity constraint are obtained. Feasible solutions are proposed to SLB for the identified implementation challenges of Adexa.